Male Bonding in Shakespeare's Plays - Aguirre, Beatriz (Íkala, Revista de Lenguaje y Cultura, 1998)
Shakespeare throughout his plays, tradegies and comedies, makes an ample representation of male bonding at different levels, and although he shows predilection for this kind of relationship he never idealizes it. Shakespeare is aware of human weakness. Each group of male friends functions differently because, although they express similar bonding, the exchanging of experiences varies in its content as well as h its form. What is evident is that friendship survives more often than love.